Movie’s box office performance prediction: An approach based on movie’s script, text mining and deep learning - Sá, Rafael Castilho Corrêa de (2020)
Dissertation presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Knowledge Management and Business Intelligence